1999
DOI: 10.1542/peds.104.4.931
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Physician Financial Incentives and Feedback to Improve Pediatric Preventive Care in Medicaid Managed Care

Abstract: Feedback to physicians, with or without financial incentives, did not improve pediatric preventive care in this Medicaid HMO during a time of rapid, secular improvements in care. Possible explanations include the context and timing of the intervention, the magnitude of the financial incentives, and lack of physician awareness of the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
127
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 9 publications
0
127
0
1
Order By: Relevance
“…Three studies (Grady et al 1997;Hillman et al 1998;Hillman et al 1999) didn't detect any significant effect of P4P bonus rewards or bonus rewards combined with performance feedback on physician compliance with cancer screening, pediatric immunization and mammography referrals. Two studies (Fairbrother et al 1999;Fairbrother et al 2001) found that a bonus or bonus with performance feedback incentives increased documented coverage levels for childhood immunization, but the measured increase 6 was primarily due to better documentation not better immunization practices.…”
Section: Empirical Evidence On Physician Response To P4pmentioning
confidence: 97%
“…Three studies (Grady et al 1997;Hillman et al 1998;Hillman et al 1999) didn't detect any significant effect of P4P bonus rewards or bonus rewards combined with performance feedback on physician compliance with cancer screening, pediatric immunization and mammography referrals. Two studies (Fairbrother et al 1999;Fairbrother et al 2001) found that a bonus or bonus with performance feedback incentives increased documented coverage levels for childhood immunization, but the measured increase 6 was primarily due to better documentation not better immunization practices.…”
Section: Empirical Evidence On Physician Response To P4pmentioning
confidence: 97%
“…Hutchison et al (1996), for example, show that Canadian physicians paid via capitation and a supplementary incentive payment for low hospital utilization rates do not have significantly lower hospital admission rates among their patients than physicians paid exclusively via FFS. Similarly, Hillman et al (1998) and Hillman et al (1999) do not observe a significant effect of P4P incentives coupled with performance feedback on physician compliance with cancer screening and pediatric preventive care guidelines in a U.S. Medicaid Health Maintenance Organization (HMO). A study by Strong et al (2009) reports that the U.K. Quality and Outcomes Framework (QOF), the most comprehensive P4P program to date, does not lead to an improvement in the quality of ambulatory care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pay-forperformance had the greatest effect on low rather than high performers [3,9,16,33,44,64,72]. Approaches with purely positive incentives (versus winners and losers) [12,16,34,35,48] and paying clinicians rather than hospitals were more effective [16,61]. Pay-for-performance focused on the individual provider found no relationship between frequency [17] and size of incentive on effect sizes [72].…”
Section: Search Strategies and Criteriamentioning
confidence: 93%
“…The answer to the first question was, in most cases, a qualified yes; only three studies [34,35,65] did not report improvement. However, the overall effect was small and highly context-specific [16,28,49,61,66,67,72].…”
Section: Search Strategies and Criteriamentioning
confidence: 98%